KEMAMPUAN SISWA KELAS VIII SMP NEGERI 15 BANDA ACEH MENULIS IKLAN BARIS - Muhammad Idham; Armia Armia; Sarah Aulia (Jurnal Dedikasi Pendidikan, 2023)
This study aims to describe the ability of class VIII students of SMP Negeri 15 Banda Aceh to write classified ads based on language aspects, content completeness aspects, and writing length aspects. This type of research is descriptive research with a quantitative approach. Data was collected by assignment technique in which students were asked to write classified ads based on the objects provided. Data analysis using simple statistical analysis. The results showed that the average value of writing classified ads based on language aspects was 73.2 and included in the good category. The average score obtained by students writing classified ads based on the completeness aspect of the content is 96.3 and is included in the very good category. The average score obtained by students writing classified ads based on the long aspect of writing is 78.5 and is included in the good category. The overall average value is 81.1 and is in the good category. Thus, the conclusion of this study is that the ability of class VIII students of SMP Negeri 15 Banda Aceh to write classified ads is included in the good category.